A new species of freshwater crab of the genus Microthelphusa (Brachyura: Pseudothelphusidae) from a remote isolated cloud forest on a tabletop mountain in western Guyana, South America - Cumberlidge, Neil (Zootaxa, 2007)
A new species of freshwater crab of the genus Microthelphusa Pretzmann, 1968, from Guyana, South America is described.  Microthelphusa meansi, new species, was collected from a remote isolated cloud forest in the Wokomung Massif, a tabletop mountain (tepui) in western Guyana at over 1,000 m above sea level.  The conspicuous horseshoe-like marginal lobe and the dome-like auxiliar cephalic lobe of the first gonopod clearly distinguish this species from all 12 congeners.